No effect of generalized joint hypermobility on injury risk in elite female soccer players: A prospective cohort study - Blokland, D.; Thijs, K. M.; Backx, F. J. G.; Goedhart, E. A.; Huisstede, B. M. A. (The American Journal of Sports Medicine, 2017)
Background: Although it has been suggested that generalized joint hypermobility (GJH) is a risk factor for injury in soccer players, it remains unclear whether this applies to elite female soccer players. Purpose: To investigate whether GJH is a risk factor for injury in elite female soccer players. Study Design: Cohort study; Level of evidence, 2. Methods: Elite female soccer players in the Netherlands were screened at the start of the 2014-2015 competitive season. GJH was assessed using the Beighton score. Soccer injuries and soccer exposure were registered throughout the entire season. Poisson regression was performed to calculate incidence risk ratios (IRRs) using different cutoff points of the Beighton score (=3, =4, and =5) to indicate GJH. Results: Of the 114 players included in the study, 20 were classified as hypermobile (Beighton score =4). The mean (±SD) injury incidence per player was 8.40 ± 9.17 injuries/1000 hours of soccer, with no significant difference between hypermobile and nonhypermobile players. GJH was not a risk factor for injuries when using Beighton score cutoff points of =3 (IRR = 1.06 [95% CI, 0.74-1.50]; P = .762), =4 (IRR = 1.10 [95% CI, 0.72-1.68]; P = .662), or =5 (IRR = 1.15 [95% CI, 0.68-1.95]; P = .602). Similarly, GJH was not a significant risk factor for thigh, knee, or ankle injuries evaluated separately. Conclusion: This study indicates that GJH is not a risk factor for injuries in elite female soccer players, irrespective of Beighton score cutoff point. Hypermobile players at this elite level might have improved their active stability and/or used braces to compensate for joint laxity.